2018
DOI: 10.1002/jor.23902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mitomycin C on recurrence of plantar fibromas

Abstract: Although certainly not the first line treatment for plantar fibromas, surgical resection is a treatment option for some patients with have failed exhaustive non-surgical treatment. The use of topical Mitomycin C has been recently shown to reduce the recurrence rate of other fibrous lesions. The purpose of this study was to determine the impact of topical application of Mitomycin C on recurrence rate of plantar fibromas. A retrospective analysis was done from a prospectively gathered database with a total 50 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…In the research by Amer et al [74], after the excision of the plantar nodules, they used topical Mitomycin C (6cc, 0.4 mg/mL) on the tumor bed for five minutes. The results were completely unexpected: there was no recurrence rate of plantar nodules when topical Mitomycin C was associated with surgical resection compared to the surgical treatment alone.…”
Section: Mitomycin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research by Amer et al [74], after the excision of the plantar nodules, they used topical Mitomycin C (6cc, 0.4 mg/mL) on the tumor bed for five minutes. The results were completely unexpected: there was no recurrence rate of plantar nodules when topical Mitomycin C was associated with surgical resection compared to the surgical treatment alone.…”
Section: Mitomycin Cmentioning
confidence: 99%
“…It has been observed that the recurrence rate following excision is around 60% [80], with some findings claiming that phenobarbital, in epileptic patients, could augment the chances of recurrence [89]. According to one study, females with larger tumors have a greater probability of recurrence [74].…”
Section: Recurrence Rate After Excisionmentioning
confidence: 99%